Kepemimpinan Kepala Madrasah dalam Meningkatkan Kualitas Pendidikan di Madrasah Ibtidiyah - Maulidayani Maulidayani (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of this study is to find out how the leadership of the Madrasah Head in improving the quality of education in MIN 3 Medan City. This study uses qualitative research, namely data derived from interview scripts, field notes, personal documentation, memo notes, and other official documents. The type of research used is a case study. This research uses a single case study. The results of this study are that in carrying out his leadership, the Head of MIN 3 Medan City mostly applies the democratic leadership type. However, it is possible for the Head of Madrasah MIN 3 Medan City to carry out his leadership by applying the autocratic type. 1. The efforts of the Head of Madrasah in improving the quality of Education in MIN 3 Medan City include the following efforts: a. Provide teaching materials b. Improving the quality of educators. c. Habituations (Hidden Curriculum) 2. The role of the Head of Madrasah in improving the quality of education at MIN 3 Medan City includes 2 roles, namely: Head of Madrasa as administrator and as supervisor Keywords: Leadership, quality of education